2005
DOI: 10.1158/1055-9965.epi-04-0798
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Low Benzene Exposure: Comparative Evaluation of Urinary Biomarkers, Influence of Cigarette Smoking, and Genetic Polymorphisms

Abstract: Benzene is a human carcinogen and an ubiquitous environmental pollutant. Identification of specific and sensitive biological markers is critical for the definition of exposure to low benzene level and the evaluation of the health risk posed by this exposure. This investigation compared urinary trans,trans-muconic acid (t,t-MA), Sphenylmercapturic acid, and benzene (U-benzene) as biomarkers to assess benzene exposure and evaluated the influence of smoking and the genetic polymorphisms CYP2E1 (RsaI and DraI) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 47 publications
10
67
1
Order By: Relevance
“…Therefore, the finding of values in excess of the 5 µg/m 3 threshold during sampling lasting 8 hours does not necessarily indicate a raised health risk. As regards the influence of a smoking habit, previous studies have demonstrated that the benzene concentrations measured with personal samplers do not reflect the true level of exposure to benzene induced by cigarette smoke (Fustinoni et al, 2005;. The results of the present study partly confirm reports in literature, since a smoking habit did not affect the percentage of benzene determinations exceeding the LOD, and no correlation was observed between airborne benzene and the number of cigarettes smoked during the sampling period.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Therefore, the finding of values in excess of the 5 µg/m 3 threshold during sampling lasting 8 hours does not necessarily indicate a raised health risk. As regards the influence of a smoking habit, previous studies have demonstrated that the benzene concentrations measured with personal samplers do not reflect the true level of exposure to benzene induced by cigarette smoke (Fustinoni et al, 2005;. The results of the present study partly confirm reports in literature, since a smoking habit did not affect the percentage of benzene determinations exceeding the LOD, and no correlation was observed between airborne benzene and the number of cigarettes smoked during the sampling period.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, these experiences have been gained largely in workers such as traffic wardens or public transport drivers who have occupational exposure to road traffic and so to generally higher concentrations of benzene than those affecting the general population Campo et al, 2011;Fustinoni et al, 2005;Manini et al, 2008). In this work the three main biological markers of internal dose currently in use, or under study for validation in biological monitoring of exposure to benzene, namely t,t-MA, SPMA and urinary benzene, were studied.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation
“…It is also present in cigarette smoke. Therefore, this compound, found in cigarette smoke and other products, may cause concerns for public health (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…In occupational studies, levels of VOCs and their metabolites in breath, blood and urine tend to be highly correlated with the corresponding air levels (Rappaport et al, 2002;Egeghy et al, 2003;Fustinoni et al, 2005). However, relationships between concentrations of VOCs in the general environment and the corresponding biomarker levels have been ambiguous (Lin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%